Bronchial carcinoid tumor managed with bronchial artery embolization before endobronchial resection: A case report - Kajikawa, Shigehisa (Thorac Cancer, 2021)
Endobronchial resection using a bronchoscope is often selected as treatment for carcinoid tumors located in the central airways. However, massive bleeding is one of the most serious complications during bronchoscopic surgery. Here, we report the case of a 77‐year‐old female with a typical carcinoid tumor located in the right truncus intermedius who underwent bronchial artery embolization (BAE) one day before endobronchial intervention using a flexible bronchoscope. The tumor was successfully resected without bleeding. BAE prior to endobronchial resection of carcinoid tumors may be useful for reducing the risk of bleeding.